Hypoglycemic effect of consumption of yacon (yacón) in type 2 diabetic mice induced with alloxan - Mejía Vásquez, América (2019)
Objective: Determine the effectiveness of the consumption of yacon (Smallantus sonchifolius) on glucose levelsin diabetes mellitus type 2 with alloxan-induced albino mice. Methods: The sample was comprised of a controlgroup and treatment with 21 albino mice in each case, with weights averages between 30 - 40g, executed in thelaboratory of Anatomy and microscopy. The mice were induced with Alloxan in solution of 0.5gr / 200 ml ofdistilled water administered intraperitoneally at doses of 0.1 to 0.7 ml/36 days to induce to DM2. The averageevaluation of basal glucose was 110 mg/dl for control and treatment. Results: In the treatment group inducedinitial glucose levels was 135.30 mg/dl, reduced to 107,70 mg/dl, with a confidence level of 99%, presentedsignificant statistical differences in the tabulated value of (p < 01). The initial glucose and end of the controlgroup was 130.60 mg / dl and 151.45 mg / dl, respectively, had no degree of significance. Conclusions: the studyanatomy pathological by cytotoxic effect of Alloxan on the pancreas, presented malformation of structural cellsand destruction of the islets of Langerhans, also the consumption of 100g of yacon in albino mice induced toDM2 during a period of 34 days significantly decreased the level of glycemia.